2020
DOI: 10.1111/1346-8138.15220
|View full text |Cite
|
Sign up to set email alerts
|

Significant relationship between temporal hair loss and other scalp areas in female pattern hair loss

Abstract: Female pattern hair loss affects the central scalp, sparing the frontal hairline. The temporal area can also be affected by hair loss. We investigated the degree of temporal hair loss and correlation of other sites of scalp hair loss in Korean female pattern hair loss patients. A total of 109 women with female pattern hair loss were enrolled in this retrospective analysis. We measured hair density and thickness in five scalp sites including the frontal, vertex, occipital and bilateral temporal areas by phototr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
(63 reference statements)
1
5
0
Order By: Relevance
“…Hair density in this study showed a similar value to the previous study in Southern Chinese women (15). However, when comparing with other studies on Asian women including Korean and Thai women, the hair density of Chinese normal participants was a little bit lower and much lower than Caucasians, Hispanics and Africans (13,(27)(28)(29). In terms of hair shaft diameter, our results also seemed to be much "lower" than other similar studies except for the study of Caucasians women conducted by Rakowska et al (9).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Hair density in this study showed a similar value to the previous study in Southern Chinese women (15). However, when comparing with other studies on Asian women including Korean and Thai women, the hair density of Chinese normal participants was a little bit lower and much lower than Caucasians, Hispanics and Africans (13,(27)(28)(29). In terms of hair shaft diameter, our results also seemed to be much "lower" than other similar studies except for the study of Caucasians women conducted by Rakowska et al (9).…”
Section: Discussionsupporting
confidence: 82%
“…The variation of the results in different studies may be caused by different devices and manners for the studies. Most of the previous study included about five randomly selected terminal hairs for hair shaft diameter measurement under 100-fold magnification, using trichoscopy system Folliscope R (LeedM Corporation) (13,28). While in our study and Rakowska et al (9) study, vellus hair was also included in the diameter measurement.…”
Section: Discussionmentioning
confidence: 95%
“…The temporal involvement in this study is evident in female hair loss. We propose that temporal involvement should be added to the pattern hair loss classification, especially the BASP classification 29 . As a result of applying scalp massage for 15 and 25 min to female office workers, positive effects were observed on stress hormones, blood pressure, and heart rate.…”
Section: Resultsmentioning
confidence: 99%
“…We propose that temporal involvement should be added to the pattern hair loss classification, especially the BASP classification. 29 As a result of applying scalp massage for 15 and 25 min to female office workers, positive effects were observed on stress hormones, blood pressure, and heart rate. Therefore, scalp massage can be used for stress control without any spatial or temporal limitations.…”
Section: Several Main Causes and Types Of Scalp And Hair Lossmentioning
confidence: 99%
“…and parietal scalp is of neural crest origin, while that of the occipital scalp is of mesodermal origin. 24,25 Follicular units from different regions of the scalp vary in their susceptibility to undergo terminal to vellus hair transformation, leading to macroscopic and microscopic patterns of hair loss, respectively. 26 In our observation, there were a small quantity of FPHL patients who presented with serious hair loss in the parietal area.…”
mentioning
confidence: 99%